(untitled) (Physical Sciences and Technology, 2017)
The reaction γ + pps → p + p, where diproton pps is a proton pair in 1S0 state, is a spin-isospin partner of the fundamental reaction of deuteron photodisintegration. The inverse reaction, the hard bremsstrahlung p + p → γ + pps, has been observed with the ANKE spectometer at COSY-Jülich. In addition to differential cross section measured earlier, in this work it’s analyzing power has been measured at forward angles at several energies in the region of Δ(1232) isobar exictation.